Reinvenção da cultura popular na música de Beto Brito: uma abordagem semiótica - Régis, Líllian da Cruz (2012)
The present study aims to examine how the singer, songwriter and rabequeiro piauiense Beto Brito uses popular culture in his compositions. We understand popular culture as dynamic tradition in which they operate changes of each historical and social moment. However, the popular genres are not fixed or immutable. Our objective is to see how Beto Brito updates the tradition element of popular culture into their musical compositions. To achieve our goals, we analyzed the songs Zabé, Ciranda mei-de-feira and Bazófias, grounded in Semiotics Greimas (Greimas A.J.) and the Semiotics of Song (Luiz Tatit).